Optimizing the social media promotion strategy to improve the branding of Putak Tourism Villages - Dwi Martiyanti; Muhammad Heldir; Pandu Aditya; Ryan Wiranata; Kenny Mandala Chandra Tjiang; Richard (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Tourism villages have contributed to improving the community economy, but the lack of optimal digital support for promotion has resulted in low visibility and popularity of tourism village destinations. Putak Tourism Village is one of those still experiencing this problem. The lack of knowledge and skills to optimize social media as a promotional medium remains an obstacle. This community service aims to optimize promotional strategies through social media to improve the branding of Putak Tourism Village. This community service activity is carried out through training and mentoring partners, using Instagram social media as a promotional strategy. The result of this program is an increase in the majority of Putak Tourism Village managers' understanding (86 percent understand) regarding the strategy for increasing tourism village branding through Instagram social media. The implication of this program shows that enhancing digital literacy through targeted social media training can significantly improve promotional capabilities and destination branding, thereby potentially increasing tourist visits and supporting the sustainable development of local tourism economies.